2015
DOI: 10.1182/blood.v126.23.4206.4206
|View full text |Cite
|
Sign up to set email alerts
|

High GRP78 (78-kDa Glucose-Regulated Protein) Expression Predicts for a Favorable Clinical Outcome in Patients with Multiple Myeloma and May be a Potentially Useful Therapeutic Target in the Treatment of Multiple Myeloma

Abstract: Background: GRP78 (78-kDa glucose-regulated protein) is a molecular chaperone that is upregulated during cellular stress. It has been well demonstrated that GRP78 upregulation is associated with chemoresistance and metastasis in solid tumours. GRP78 has not been widely explored in multiple myeloma (MM), however, we and others have shown that GRP78 is much more overexpressed in myeloma cell lines compared to other cell lines. To assess the clinical relevance of GRP78 overexpression in MM, we investigated the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The discovery that GRP78 can determine whether IGFBP-3 is pro or anti-tumorigenic paves a new way for clinical prognosis. Clinically, high GRP78 levels have been associated with more aggressive features and worse prognosis in various cancers in many studies [ 29 , 30 , 31 , 32 , 33 ] however, contradictory results have also been reported [ 34 , 35 , 36 ]. Our results indicating that the function of IGFBP-3 is either pro- or anti-tumorigenic depending on levels of GRP78, suggest that the key to improving the clinical outcome of patients is to implement measurement of both markers in breast tumours in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery that GRP78 can determine whether IGFBP-3 is pro or anti-tumorigenic paves a new way for clinical prognosis. Clinically, high GRP78 levels have been associated with more aggressive features and worse prognosis in various cancers in many studies [ 29 , 30 , 31 , 32 , 33 ] however, contradictory results have also been reported [ 34 , 35 , 36 ]. Our results indicating that the function of IGFBP-3 is either pro- or anti-tumorigenic depending on levels of GRP78, suggest that the key to improving the clinical outcome of patients is to implement measurement of both markers in breast tumours in clinical practice.…”
Section: Discussionmentioning
confidence: 99%